Expression, purification and crystallization of the ammonium transporter Amt-1 from Archaeoglobus fulgidus - Andrade, Susana L. A. (International Union of Crystallography, 2005)

(untitled)
Ammonium transporters (Amts) are a class of membrane-integral transport proteins found in organisms from all kingdoms of life. Their key function is the transport of nitrogen in its reduced bioavailable form, ammonia, across cellular membranes, a crucial step in nitrogen assimilation for biosynthetic purposes. The genome of the hyperthermophilic archaeon Archaeoglobus fulgidus has been annotated with three individual genes for ammonium transporters, amt1–3, the roles of which are as yet unknown. The amt1 gene product has been produced by heterologous overexpression in Escherichia coli and the resulting protein has been purified to electrophoretic homogeneity. Crystals of Amt-1 have been obtained by sitting-drop vapour diffusion and diffraction data have been collected.